P-glycoprotein-mediated resistance to chemotherapy in cancer cells: using recombinant cytosolic domains to establish structure-function relationships - Di Pietro,A. (1999)
Resistance to chemotherapy in cancer cells is mainly mediated by overexpression of P-glycoprotein (Pgp), a plasma membrane ATP-binding cassette (ABC) transporter which extrudes cytotoxic drugs at the expense of ATP hydrolysis. Pgp consists of two homologous halves each containing a transmembrane domain and a cytosolic nucleotide-binding domain (NBD) which contains two consensus Walker motifs, A and B, involved in ATP binding and hydrolysis. The protein also contains an S signature characteristic of ABC transporters. The molecular mechanism of Pgp-mediated drug transport is not known. Since the transporter has an extraordinarily broad substrate specificity, its cellular function has been described as a "hydrophobic vacuum cleaner". The limited knowledge about the mechanism of Pgp, partly due to the lack of a high-resolution structure, is well reflected in the failure to efficiently inhibit its activity in cancer cells and thus to reverse multidrug resistance (MDR). In contrast to the difficulties encountered when studying the full-length Pgp, the recombinant NBDs can be obtained in large amounts as soluble proteins. The biochemical and biophysical characterization of recombinant NBDs is shown here to provide a suitable alternative route to establish structure-function relationships. NBDs were shown to bind ATP and analogues as well as potent modulators of MDR, such as hydrophobic steroids, at a region close to the ATP site. Interestingly, flavonoids also bind to NBDs with high affinity. Their binding site partly overlaps both the ATP-binding site and the steroid-interacting region. Therefore flavonoids constitute a new promising class of bifunctional modulators of Pgp.